2005
DOI: 10.1055/s-2005-872923
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic and Biochemical Evidence for the Cardioprotective Effect of Vitamin E in Doxorubicin-Induced Acute Cardiotoxicity in Rats

Abstract: Vitamin E pretreatment prevented the PR, QT, and ST segment changes caused by doxorubicin. Vitamin E treatment helped to decrease the levels of CPK-MB and LDH that were increased due to myocardial damage caused by the doxorubicin. There is sufficient evidence to believe that vitamin E protects the rat myocardium from doxorubicin-induced damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
26
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 2 publications
6
26
0
1
Order By: Relevance
“…15) Other's study showed that EDA (3 mg/kg) effectively prevented DOX-induced chronic cardiac deterioration. 8) In agreement with other findings, [9][10][11] the acute cardiotoxicity of DOX (1.5 mg/kg) in dogs was characterized by conduction abnormalities (including decreased heart rate, ST segment elevation, QT intervals prolongation, inverted T wave, arrhythmia, and myocardial ischemia) and increased serum CK and AST. The serum CK and AST reached apogee at 24 h and dropped to baseline in 48-72 h after myocardial damage.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…15) Other's study showed that EDA (3 mg/kg) effectively prevented DOX-induced chronic cardiac deterioration. 8) In agreement with other findings, [9][10][11] the acute cardiotoxicity of DOX (1.5 mg/kg) in dogs was characterized by conduction abnormalities (including decreased heart rate, ST segment elevation, QT intervals prolongation, inverted T wave, arrhythmia, and myocardial ischemia) and increased serum CK and AST. The serum CK and AST reached apogee at 24 h and dropped to baseline in 48-72 h after myocardial damage.…”
Section: Discussionsupporting
confidence: 74%
“…9,10) As shown in Fig. 2, dosing LBP or EDA daily has no significant effect on the durations of the electrocardiographic parameters.…”
Section: General Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro electrophysiological studies showed that supra-therapeutic doses of risperidone induced the prolongation of ventricular repolarization in a dose-related and reverse use-dependent manner, which prolonged the terminal repolarization period [7,8]. Electrocardiographic (ECG) measures of heart rate, the PR interval, the QT interval and the QRS interval are usually used to evaluate acute cardiotoxicity [5,9,10]. Administration of the non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist 5R,10S-(+)-5-methyl-10,11-dihydro-5H-dibenzocyclohepten-5,10-imine hydrogen maleate (MK-801) to rats and mice is often used to create an experimental model of schizophrenia.…”
mentioning
confidence: 99%
“…Pharmacodynamic study showed that PDs significantly reduced MK-801-induced hyperlocomotion in mice. The electrocardiogram (ECG) was recorded at 0,5,10,15,20, 25, 30, 45 and 60 min. in anaesthetized rats after i.v.…”
mentioning
confidence: 99%